KUALITAS BAKTERIOLOGIS PERALATAN MAKAN DAN PERILAKU PEDAGANG KAKI LIMA DI SENTRA WISATA JAMBANGAN SURABAYA TAHUN 2016 - Emmy Laskar Pratiwi; Umi Rahayu; Winarko . (Poltekkes Kemenkes Surabaya, 2016)
Food safety is an effort to control the risk factors of contaminations on food both come from food ingredients, people, places and equipment in order to be safe to consume. The purpose of this study was to determine the Behavior of sidewalk merchants and the bacteriological quality of eating equipments in the Jambangan Tourism Center of Surabaya City. This research is descriptive research with cross sectional approach. Data collection was by means of observation, interviews and laboratory tests. Total sample of 20 merchants. Data were analyzed descriptively in narrative form and tables. The results of research showed that the behavior of the food and drink merchants in the Jambangan Sidewalk Merchants Tourism Center of Surabaya as much as 75% behave good and 25% behave reasonably. The wipe test results of eating equipments in parameter Escherichia coli if compared with the Decree of Indonesian Health Ministry No. 1098/Menkes/VI/2003 showed that there are two stands positive Escherichia coli. It can be concluded that from the 20 merchants surveyed, 15 merchants (75%) behave well, five traders (25%) behave fairly and on wipe examination of eating tools there are 2 stands positive Escherichia coli. It is recommended in order that merchants apply the personal hygiene and provide 3 sinks for equipments and at drying use a clean cloth specifically for eating and drinking tools. Keywords : Merchant behavior, bacteriological quality, tool wipe